Unlocking the Secret of Bio-additive Components in Rubber Compounding in Processing Quality Nitrile Glove - Yew, G.Y. (Springer, 2020)
The sustainability of nitrile glove production process is essential both in the financial and energy perspective. Nitrile glove has the lowest material cost with positive mechanical and chemical performance quality for the disposable glove market. Nitrile glove also holds a major market in disposable gloves sector, and nitrile rubber compounds may contribute to the huge reduction of the capital cost for a pair of surgical gloves due to the inexpensive raw material compares with other synthetic polyisoprene or neoprene. Hence, blending of bio-additive into the nitrile latex might support the 3 pillars of sustainability for environmental, societal, and financial sector. Bio-additives helps increase the degradation rate of gloves under natural conditions. Bio-based substances could be derived from food waste, natural plants, and aquatic plants like micro- and macro algae. Furthermore, antimicrobial agent (e.g. brilliant green and cyclohexadiene) is the trend in surgical glove for coated as protecting layer, due to the capability to remove pathogens or bacterial on the surgeon hands during operation period. Besides, the section in energy recovery is a proposing gateway for reducing the financial cost and makes the process sustainable. Â© 2020, Springer Science+Business Media, LLC, part of Springer Nature.